Obtenção de estruturas a base de BiPO4 e suas aplicações como supercapacitores - MONTELES, Iara Araujo (2022)
This work seeks to understand the influence of bismuth phosphate (BiPO4) structural phases on its electrochemical performance as an electrode material for supercapacitors. BiPO4 structures were obtained via template method using ethyleneglycol (EG), cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS). Structural characterizations were performed by X-Ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Dispersive X-Ray Spectroscopy (EDX). The X-Ray Diffraction Patterns (PDRX), for the samples obtained with Ethylene Glycol, CTAB and SDS, were indexed for hexagonal structure, while for the sample obtained without the presence of templates, it presented a monoclinic structure. For structure obtained in ethylene glycol, a mixture of structure, monoclinic/hexagonal, was observed, data that were confirmed with Raman spectroscopy analyses. Scanning electron microscopy images showed that, for samples obtained with templates, different morphologies were presented. While for the sample obtained without using surfactant, morphology like rectangular rods of different sizes were observed, data that were confirmed by transmission electron microscopy. The EDX analyzes corroborate the presence of constituent elements of the synthesized materials. The electrochemical behavior was measured by Cyclic Voltametry, Galvanostatic Charge and Discharge, Cyclic Stability and Electrochemical Impedance Spectroscopy. The electrochemical analyzes confirmed the pseudocapacitive behavior of the material. The specific capacitance values were calculated and show that the homostructured material obtained a higher value when compared to the others presented in this work. This one had a specific capacitance value of 173.84 F.g-1 at a current density of 1 A.g-1 and indicated a significantly efficient stability, retaining 50% of the initial specific capacitance after 1000 cycles under a current density of 10 A.g-1.